Application of the Simplex Lattice Design Method to Determine the Optimal Formula of Diclofenac Sodium Nanoemulsion - Nahdhia, Nadhifatun; M. Agus Syamsur Rijal; Esti Hendradi; Riyanto Teguh Widodo (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: The success of nanoemulsion preparation, with the aim of producing good characteristic values, is determined by the ratio of each component. The design of experiments (DoE) approach using the Simplex Lattice Design (SLD) method can be used to determine the optimal formula for nanoemulsions, with variable factors consisting of oleic acid, Tween 20:ethanol (4:1), and water. The observed response variables included droplet size, PDI, and pH. Objective: DoE can help reduce the energy, cost, and time needed to make the optimal formula for diclofenac sodium nanoemulsions. Methods: Nanoemulsions were prepared using low-energy emulsification. Their characteristics were evaluated and analyzed using Design Expert software. Results: The optimal nanoemulsion formulation consisted of 4.17% oleic acid, 37.5% emulsifier (Tween 20: ethanol, 4:1), and 58.33% water. The nanoemulsion characteristics were good, with 20.37 a droplet size, 0.42 PDI, of 4.75 pH. The observed values were not significantly different from the predicted values, and the formula could effectively trap 1% diclofenac sodium. Conclusion: The simplex lattice design method is very useful for pharmaceutical development, such as nanoemulsion optimization.